Stereotactic body radiation therapy for the treatment of lymph node metastases: a retrospective mono-institutional study in a large cohort of patients - Caivano, Donatella; Bonome, Paolo; Pezzulla, Donato; Rotondi, Margherita; Sigillo, Riccardo Carlo; De Sanctis, Vitaliana; Valeriani, Maurizio; Osti, Mattia Falchetto (Frontiers in Oncology, 2023)
Introduction: Lymph node metastases (NMs) are a common site of tumor spread that can occur at different time of disease. Stereotactic Body Radiation Therapy (SBRT) can be a therapeutic option for the treatment of NMs in the setting of oligometastatic disease (OMD). Aim of this study was to evaluate as primary end points the Local Control (LC) and secondary end points the Loco Regional Nodal Control (LRNC), Distant Nodal Control (DNC), Distant Metastasis Free Survival (DMFS), Progression Free Survival (PFS), Overall survival (OS) and concurrently to assess the predictive factors of response.Methods: This is a retrospective study that analyzes a group of patients treated with SBRT on NMs from different primary tumors, with a of maximum 5 metastasis. Treated lesions were divided into 4 groups: oligometastatics, oligorecurrents, oligoprogressives and oligopersistents.Results: From 2007 to 2021, 229 NMs were treated in 174 patients with different primary tumor. The schedule most represented was 30 Gy in 5 fractions. The LC was obtained in 90% of NMs treated by SBRT with rates at 1-, 3-and 5-years of 93%, 86% and 86% respectively. The LRNC was reached in 84% of cases with rates at 1-, 3-and 5-years of 88%, 83% and 77% respectively. The DNC was obtained in 87% of cases with rates at 1-, 3-and 5-years of 92%, 82% and 78% respectively. The DMFS was obtained in 38% of cases with rates at 1-, 3-and 5-years of 57% 40% and 30% respectively. The rate of PFS were 44%, 23% and 13% at 1-, 3 -and 5-years respectively. The rates at 1-, 3-and 5-years of OS were 78%, 48% and 36% respectively.SBRT is an option for the treatment of NMS, whit high rates of LC, improving survival, with a good safety and tolerance. Tumor volume, tumor burden, lesion site and doses can be predictive factors of response, however, multi-institutional studies with a greater number of patients could be helpful to better select patients and understand the right integrations between ablative treatment and systemic therapies.